Building information modeling for indoor environmental performance analysis - Lim, Yaik Wah (2015)
There are increasing numbers of Building Information Modeling (BIM) software available nowadays which change the working methods in Architecture, Engineering and Construction (AEC) industry. From the stages of building design development to post-occupancy management, BIM plays an essential role in collaboration among multi-discipline professions, time and cost saving, fabrication and construction as well as facilities management. With the arising concern for sustainability in built environment, BIM software is also developed to simulate building indoor environmental performances. The aim of this study is to review the latest development of BIM-based indoor environmental performance analysis for sustainable building design. Various state-of-the-art BIM-based sustainability tools which are commonly employed by AEC industry are reviewed and compared in relation with design parameters and performance outputs. The advantages and disadvantages of the software are analyzed. The comparison allows proper selection of software which determines the effectiveness and reliability of simulation process and outputs. The prospects of BIM development and its applications for indoor environmental studies are also discussed. The review concludes that BIM-based sustainability simulation during early or pre-design stage is very crucial to develop sustainable building design. Further research on the framework and guidelines for BIM-based sustainability analyses and design process shall be conducted.